2001
DOI: 10.1107/s0108270100019867
|View full text |Cite
|
Sign up to set email alerts
|

trans-Bis(ethanolamine-N,O)bis(saccharinato-N)copper(II)

Abstract: In the title complex, [Cu(C(7)H(4)NO(3)S)(2)(C(2)H(7)NO)(2)], the Cu(II) centre lies on an inversion centre and exhibits octahedral coordination, with the two ethanolamine (Hea) and two saccharinate [sac; anionic 1,2-benzisothiazol-3(2H)-one 1,1-dioxide] ligands in a trans configuration. The bidentate Hea ligands bridge axial and equatorial positions and the sac anions occupy equatorial sites around the distorted octahedral copper(II) centre [Cu--O = 2.3263 (16), Cu--N(Hea) = 1.9923 (16) and Cu--N(sac) = 2.177… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous studies showed that all the aqua complexes of sac with first-row divalent transition metal ions consist of neutral [M(sac) 2 (H 2 O) 4 ] AE 2H 2 O complexes, containing only two coordinated sac ligands in the trans positions within the coordination sphere [6][7][8][9][10][11][12][13]. Furthermore, mixed-ligand sac complexes of transition metals prepared by us or other groups also contain one or two sac ligands, depending on steric hindrance of the co-ligands [17][18][19][20][21][22][23][24][25][26][27][28][29], and the presence of three sac ligands in the primary coordination sphere is unusual. Therefore, the most interesting aspect of complexes (1) and (2) is the coordination of three sac ligands around the copper(II) and zinc(II) ions and the complexes (1) and (2) are the first examples, exhibiting three coordinated sac ligands in the same coordination polyhedron of a mononuclear unit.…”
Section: Synthesismentioning
confidence: 99%
“…Previous studies showed that all the aqua complexes of sac with first-row divalent transition metal ions consist of neutral [M(sac) 2 (H 2 O) 4 ] AE 2H 2 O complexes, containing only two coordinated sac ligands in the trans positions within the coordination sphere [6][7][8][9][10][11][12][13]. Furthermore, mixed-ligand sac complexes of transition metals prepared by us or other groups also contain one or two sac ligands, depending on steric hindrance of the co-ligands [17][18][19][20][21][22][23][24][25][26][27][28][29], and the presence of three sac ligands in the primary coordination sphere is unusual. Therefore, the most interesting aspect of complexes (1) and (2) is the coordination of three sac ligands around the copper(II) and zinc(II) ions and the complexes (1) and (2) are the first examples, exhibiting three coordinated sac ligands in the same coordination polyhedron of a mononuclear unit.…”
Section: Synthesismentioning
confidence: 99%
“…We observed that the coordination behavior of the sac anion is mainly due to the presence of other co-ligands. The sac anion is directly bonded to the metal ions in some mixed-ligand metal complexes with monoethanolamine [3][4][5][6], diethanolamine [6,7], monoethanolethylenediamine [8] and 2-pyridylmethanol [9,10] while bulky ligands such as triethanolamine [11][12][13][14][15] and 2,6-dimethanolpyridine [16,17] usually prevent the coordination of sac, which consequently remains outside the coordination sphere as a counter-ion. In this article, we report the synthesis and, spectral characterization of new transition metal-sac complexes with 2-pyridylethanol (pyet) together with the single crystal X-ray structures of the iron (II) and copper (II) complexes.…”
Section: Introductionmentioning
confidence: 99%